Preparation and characterization of lignin-derived carbon aerogels - Jõul, Piia; Järvik, Oliver; Lees, Heidi; Kallavus, Urve; Koel, Mihkel; Lukk, Tiit (Frontiers in Chemistry, 2024)
Lignin is considered a valuable renewable resource for building new chemicals and materials, particularly resins and polymers. The aromatic nature of lignin suggests a synthetic route for synthesizing organic aerogels (AGs) similar to the aqueous polycondensation of resorcinol with formaldehyde (FA). The structure and reactivity of lignin largely depend on the severity of the isolation method used, which challenges the development of new organic and carbon materials. Resorcinol aerogels are considered a source of porous carbon material, while lignin-based aerogels also possess great potential for the development of carbon materials, having a high carbon yield with a high specific surface area and microporosity. In the present study, the birch hydrolysis lignin and organosolv lignin extracted from pine were used to prepare AGs with formaldehyde, with the addition of 5-methylresorcinol in the range of 75%–25%, yielding monolithic mesoporous aerogels with a relatively high specific surface area of up to 343.4 m2/g. The obtained lignin-based AGs were further used as raw materials for the preparation of porous carbon aerogels (CAs) under well-controlled pyrolysis conditions with the morphology, especially porosity and the specific surface area, being dependent on the origin of lignin and its content in the starting material.